The Implementation of Learning Aqidah Akhlak on Student Behavior at Madrasah Ibtidayah - Ayu Awaliyah; Anissatul Faqziaty; Anwar Mahmudi; Fiyya Zahrotul Firdausi; Muhammad Iqbaludin; Mohamad Ishak; Muhammad Yahya; Pita Andri Yani; Rika Sulastri; Salbiyah (CV. Creative Tugu Pena, 2021)
Moral and theological education plays a crucial role in shaping children's behavior. Morality, as manifested through ethical conduct, and aqidah (faith or belief) are interrelated elements that significantly influence personal development. This study aims to examine the impact of moral education and the application of aqidah on fostering positive behavior in children. Children who receive proper instruction in morality and aqidah tend to develop a positive outlook on life, form healthy social relationships, and grow into individuals who are kind, patient, and tolerant. Such education also provides a strong moral foundation that prepares them to face challenges and resist negative influences in their environment. The integration of aqidah and moral values into formal religious or character education curricula can enhance their effectiveness. Moreover, a comprehensive approach that involves families, educational institutions, and the wider community is essential in cultivating children's behavior. In conclusion, moral and theological education has a profound influence on children's development, enabling them to become ethically grounded individuals capable of contributing positively to society. Keywords: Learning Aqidah Akhlak, Student Behavior, Learning Aqidah